Effects of digital filtering technique in reducing the effects of clipping of an enhanced orthogonal frequency division multiplexing system - (Hassan, , Wan Hafiza Wan; Khatun, , Sabira (2006)
Despite of many advantages of OFDM, it has two main drawbacks which are high peak to average power ratio (PAPR) and synchronization problem. High PAPR causes saturation in power amplifiers, leading to intermodulation products among the sub carriers and disturbing out of band energy. Therefore, it is desirable to reduce the PAPR by means of PAPR reduction schemes. However, it caused the degradation of BER and enhanced the growth of out of band radiation which has led to the degradation of OFDM overall performance In this paper, OFDM system with an enhanced clipping technique has been proposed, the effects of clipping have been analyzed and the system is evaluated by integrating with its significant features including convolutional forward error control coding, oversampled inverse fast fourier transform (IFFT) and digital filtering technique in order to minimize the effects of clipping. It is shown that the bit error rate (BER) of the clipped OFDM signal is improved, the PAPR is further reduced and the effect of out of band radiation is minimized. Besides, other effects of filtering technique are also analyzed in order to optimize the overall performance of our proposed system.